Carbon-Based Nanomaterials for Biomedical Applications: A Recent Study - Maiti, Debabrata; Tong, Xiangmin; Mou, Xiaozhou; Yang, Kai (Frontiers in Pharmacology, 2019)
The study of carbon based nanomaterials (CBNs) for biomedical application has become rapidly demanding field due to their unique combinations of chemical and physical properties including thermal, mechanical, electrical, optical and structural diversity. With the help of these intrinsic properties of newly discovered auspicious CBNs, such as carbon nanotubes (CNT), graphene oxide (GO) and graphene quantum dots (GQD) have been extensively investigated in biomedical field. This review focus on the most recent studies in developing of CBNs for numerous biomedical applications, comprising bio-sensing, drug delivery and cancer therapy.